Do skiers with similar race time but different age pace similarly in a cross-country ski marathon? - Nikolaidis, P. T.; Knechtle, B. (Asian Journal of Sports Medicine, 2018)
Pacing strategies have mainly been investigated for runners, but little is known for cross-country skiers. We investigated the pacing strategies in 105,565 female and male age group athletes competing between 1998 and 2016 in the `Engadin Ski Marathon`. This race is the largest cross-country skiing marathon held in Europe covering the exact distance of a marathon. Split times are taken at the time stations 10 km (A), 20 km (B) and 35 km (C). We hypothesized to find a difference in pacing between younger and older athletes with similar race times. We calculated three percentage changes of speed, Change A (100 × (split2 - split1)/split1), Change B (100 × (split3 - split2)/split2) and Change C (100 × (split4 - split3)/split3). The men-to-women ratio was lower in the slower performance groups. In both women and men, the faster groups were more prevalent in the younger age groups and the slower groups in the older age groups; only the < 2 hours group increased speed in Change A. A non-linear variation of change in speed was observed across performance groups in Change B and C. The differences in variation of pacing by performance groups among age groups were trivial. In summary, the findings did not confirm our hypothesis that skiers of different age with similar race time would pace differently. Therefore, sex and performance, not age, should be the main criteria for coaches and skiers in order to optimize the pacing strategy in a cross-country skiing marathon.